Pengelolaan Sport Massage Menjadi Unit Bisnis Program Studi Pendidikan Jasmani Kesehatan dan Rekreasi FIK Universitas Negeri Medan - Sabaruddin Yunis Bangun; Zulpikar Ilham; Ade Ros Riza (Dharmas Journal of Sport, 2021)
ABSTRACT This research is a policy research that aims to study physical education, health and recreation, FIK Unimed in developing entrepreneurship independently and professionally, especially the sports massage clinic business. Supporting the implementation of BLU Unimed in managing a healthy business business with a sports massage clinic in the physical education, health and recreation (PJKR) study program. The hope of this activity is that many people are inspired by the existence of a sports massage clinic in the Physical Education, Health and Recreation (PJKR) study program, so that they are able to create a unique, professional and creative business needed by Students and Alumni of the Department of Physical Education, Health and Recreation (PJKR). Medan State University. This research activity is carried out by means of tutorials and discussions for theory, as well as practice/practice in groups and discussions for practical experience. The results of the research obtained are the Management of Sport Massage as a Business Unit for the Health and Recreation Physical Education Study Program, FIK State University of Medan obtained SOPs and guidelines for managing the Sport Massage Business Unit for the Health and Recreation Physical Education Study Program. The conclusion of the Sport Massage Management activity as a Business Unit for the Health and Recreation Physical Education Study Program at the State University of Medan provides various benefits of managing the entrepreneurial unit for both the Medan State University and the students of the Health and Recreation Physical Education Study Program.